Criminal Liability for The Perpetrators of TikTok Account Forgery in Indonesia - Sonya Pasaribu; Leo Lo (CV. Norma Global, 2026)
The rapid expansion of digital connectivity in Indonesia has increased exposure to identity-based cybercrime, including the creation of fake TikTok accounts. With internet penetration reaching over 78 percent of the population and more than 139 million active social media users, digital platforms have become central to economic and social interaction (APJII, 2023; We Are Social & Meltwater, 2024). This study analyzes the legal qualification of TikTok account forgery within Indonesian criminal law and examines whether such conduct fulfills the elements of criminal liability under Article 35 of the Law on Electronic Information and Transactions (ITE Law). Using a normative juridical method with statutory and conceptual approaches, the research applies grammatical, systematic, and teleological interpretation to assess the structure of the offense. The findings demonstrate that TikTok accounts qualify as Electronic Documents under Article 1 of the ITE Law and that the deliberate creation of fake accounts intended to appear authentic satisfies the objective and subjective elements of Article 35. Criminal sanctions may therefore be imposed under Article 51 paragraph (1), which provides penalties of up to twelve years’ imprisonment and substantial fines. The study further identifies enforcement challenges related to digital attribution and evidentiary standards, while affirming the normative sufficiency of the ITE Law in addressing digital identity manipulation. The research contributes to strengthening doctrinal clarity and proportional application of criminal sanctions within Indonesia’s evolving digital legal landscape.